Structural Equation Modeling of Social Media Addiction Based on Subjective Well-Being with the Mediating Role of Cognitive Emotion Regulation Difficulties - Hoseinloo, Mozhgan; Jadidi, Hooshang; JaliliShishavan, Ali (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: The aim of this study was to model the structural equation of social media addiction based on subjective well-being with the mediating role of cognitive emotion regulation difficulties. Methods and Materials: This was an applied study using a descriptive-correlational design based on structural equation modeling. From a statistical population of 98,562 undergraduate students enrolled at the North Branch of Islamic Azad University, a sample of 403 students was selected through multi-stage cluster random sampling. Participants responded to the Mobile-based Social Networks Addiction Questionnaire by Khajeh Ahmadi et al. (2016), the Subjective Well-Being Scale (SWS) by Keyes and Magyar-Moe (2003), and the Difficulties in Emotion Regulation Scale (DERS) by Gratz and Roemer (2004). Data analysis was performed using structural equation modeling in SPSS version 26 and AMOS version 24. Findings: The findings showed that the direct paths from subjective well-being (emotional, psychological, social) and cognitive emotion regulation difficulties to social media addiction were positive and statistically significant (P < .01). Subjective well-being (emotional, psychological, social) also indirectly affected social media addiction through cognitive emotion regulation difficulties; thus, cognitive emotion regulation difficulties played a mediating role in this model. Conclusion: These findings highlight that students with lower levels of subjective well-being and greater difficulties in regulating their emotions are more likely to become addicted to social media. It can be concluded that cognitive emotion regulation difficulties may serve as a key factor in preventing social media dependence and in enhancing the quality of life among students.